World Literature in Theory (Hoboken : John Wiley & Sons, 2014)
'World Literature in Theory provides a definitive exploration of the pressing questions facing those studying world literature today. Coverage is split into four parts which examine the origins and seminal formulations of world literature, world literature in the age of globalization, contemporary debates on world literature, and localized versions of world literature Contains more than 30 important theoretical essays by the most influential scholars, including Johann Wolfgang von Goethe, Hugo Meltzl, Edward Said, Franco Moretti, Jorge Luis Borges, and Gayatri Spivak Includes substantive introductions to each essay, as well as an annotated bibliography for further reading Allows students to understand, articulate, and debate the most important issues in this rapidly changing field of study '--
Includes bibliographical references and index.
Keywords: Damrosch, David; Literature -- Philosophy